The Role of Kiai Leadership and Service Quality in Shaping the Reputation of Pesantren - Hamdanah, Hamdanah; Baharun, Hasan; Najiburrohman, Najiburrohman; Thohir, Putri Fahmadia Dinda Maulida; Sanjani, M Aqil Fahmi (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
The reputation of a pesantren is closely linked to its Leadership and the quality of its educational services. The Kiai plays a central role as a moral, spiritual, and social leader, while service quality reflects the institution’s ability to meet stakeholder expectations. This study aims to examine the influence of the Kiai’s figure and service quality on the reputation of Islamic boarding schools, both partially and simultaneously. This study used a quantitative, survey-based approach. Data were collected through questionnaires distributed to 280 respondents; 224 valid responses were analyzed using simple and multiple regression tests using SPSS. The results of the study indicate that the figure of the kiai has a positive and significant influence on the reputation of Islamic boarding schools, with regression coefficients of 0.563 and 0.521 and a significance value of 0.000. Simultaneously, the figures for Kiai and service quality have a significant influence on the reputation of Islamic boarding schools (Sig. F = 0.000), explaining 41.4% of the variance in their reputation (Adjusted R² = 0.414). The standardized beta coefficient shows that the figure of the kiai (β = 0.448) has a more dominant influence than service quality (β = 0.368). The findings suggest that the synergy between strong religious Leadership and high-quality educational services shapes a pesantren's reputation. Therefore, strengthening the role of the kiai, along with continuous improvement in service quality, is crucial to maintaining the pesantren's reputation.